The Study of Process Reliability of Aircraft Engine. (2015) - Ming, Wang Ji; Min, Huang; Jun, Yi; Jun, Liu Xue
Abstract: When developing aero-engines, problems with respect to reliability maybe come because of designs, but the manufacture process causes a lot. The purpose to study the process reliability is to cut down and eliminate the process defects/failures, which will improve the pass rate. This paper puts forward the concept, evaluations, and the contents of process reliability, and method to analyze process reliability. In addition, a case will be used to certificate this analysis.